The symbiotic relationship between Symbiodinium and coral reef larvae: gene expression, fatty acid biochemistry and responses to thermal stress - Mies, Miguel (2017)
Very little is known about the association between Symbiodinium dinoflagellates, which perform the majority of primary production in coral reefs, and metazoan larvae. This thesis performed three experiments on the association between Symbiodinium and Mussismilia hispida (coral), Berghia stephanieae (nudibranch) and Tridacna crocea (giant clam) larvae. The first experiment monitored the expression of a symbiosis-specific gene in Symbiodinium clade A associated with the three larval forms during a 72-h window. The second experiment quantified the production of symbiosis-related ω3 fatty acids in Symbiodinium clades A-F also associated with the three larval hosts and the third experiment verified bleaching rates at 26, 29 and 32ºC in the larvae associated with clades A-F. The main results show that i) a symbiosis-specific gene is expressed by Symbiodinium A associated with M. hispida and T. crocea larvae, but not with B. stephanieae; ii) the DHA fatty acid is produced in significantly higher amounts by clades A and C associated with M. hispida and T. crocea larvae; and iii) that M. hispida and T. crocea larvae associated with Symbiodinium A and C have significantly lower bleaching rates. These findings suggest that clades A and C establish a more robust mutualism with M. hispida and T. crocea larvae, but there seems to be no mutualism between Symbiodinium and B. stephanieae.